1994
DOI: 10.1530/jrf.0.1010593
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of temperature-dependent immobilization of fowl spermatozoa at body temperature by an increased intracellular pH

Abstract: Fowl sperm motility was measured by altering the extracellular pH (pHe) at 30 degrees C and 40 degrees C. At 30 degrees C, the motility of intact spermatozoa was vigorous in a medium in the wide pHe range of 7.3-10.1. In contrast, intact spermatozoa were almost immotile at 40 degrees C in medium below a pHe of 8.1. However, the motility could be restored by increasing the pHe; maximum motility was obtained in medium at pHe 9.4. Stimulation of the motility of demembranated spermatozoa at 40 degrees C was also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…For instance, the percentage of motile sperm and sperm velocity were increased at alkaline pH in Turkey and quail [ 6 ]. Similar results were obtained in domestic chickens ( Gallus gallus ), and alkalinization of the external pH restored sperm motility at 40°C [ 7 , 8 ]. Huang et al (2001) reported that the sperm of Anodonta woodiana Pacifica Houde exhibited stronger motility at pH 8.5, which significantly declined at pH 7.0, 7.5, 9.5, and 10.0 [ 9 ].…”
Section: Introductionsupporting
confidence: 74%
“…For instance, the percentage of motile sperm and sperm velocity were increased at alkaline pH in Turkey and quail [ 6 ]. Similar results were obtained in domestic chickens ( Gallus gallus ), and alkalinization of the external pH restored sperm motility at 40°C [ 7 , 8 ]. Huang et al (2001) reported that the sperm of Anodonta woodiana Pacifica Houde exhibited stronger motility at pH 8.5, which significantly declined at pH 7.0, 7.5, 9.5, and 10.0 [ 9 ].…”
Section: Introductionsupporting
confidence: 74%
“…Uricotelism results in the excretion of uric acid in excretory tract but does not affect the reproductive cell indicating a potential role of pH-regulating system in avian spermatozoa. The exact role of pH along the sperm membrane is not only clear but also studies have indicated a potential role of pH on endocrine axis of birds and ultimately regulating sperm function [ 10 - 13 ]. Spermatozoa are stored for long period of time in sperm storage tubules in female birds.…”
Section: Ph Regulatory Mechanisms In Different Animalsmentioning
confidence: 99%
“…After their release, complex interaction with temperature, pH, ionic composition, and other factors occurs which regulate sperm motility. In domestic fowl, elevation in temperature from 30 to 40°C resulted in decrease motility, whereas alkalinization of external pH restored sperm motility at 40°C [ 10 ]. Similar results were shown in turkey and quail, in terms of velocity and percentage of motile spermatozoa which are increased in alkaline pH, and as compared to 30°C, 40°C requires more alkaline pH to initiate motility [ 11 ].…”
Section: Ph Regulatory Mechanisms In Different Animalsmentioning
confidence: 99%
“…Similarly, existing research has also shown that sperm movement is stimulated at a certain alkali pH range; for instance, the velocity and total motility of sperm from chickens, turkeys and quails are significantly greater at pH 8.0 compared to pH 7.0, and the sperm velocity is further increased at pH 9.0 for quail and chicken sperm (Holm and Wishart 1998). Ashizawa et al (1994) found that the increased pH may act directly on axonemal phosphoprotein, mediated by a Ca 2+ -related substance, which is likely to be a reason why sperm swimming better in the weakly alkaline environment. By contrast, as our study confirms a range of acidic to neutral pH that lead to poor sperm motion (Holm and Wishart 1998;Bonato et al 2012), which may be related to a reduction in sperm metabolism to conserve energetic resources and promote sperm lifespan (Pinto et al 1984).…”
Section: Discussionmentioning
confidence: 92%